The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.37385/jaets.v2i1.173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Acceptance Of Platform Technology Didimax Berjangka In Pekanbaru Using The UTAUT Method

Abstract: This study discusses the acceptance of PT Didimax's metatrader technology. To carry out the analysis in this study using the UTAUT method. The UTAUT method has four independent variables and two dependent variables. It is through these variables that the level of technology acceptance is explained. The results of this study from 121 respondents showed that the Performance Expectancy variable had a positive and significant impact on behavior intention, the condition t counted 3.184> t table 2015 Sig 0.002 &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Cabanillas et al (2021) stated that there was a relationship between subjective norms and gender-moderated intentions in the use of new technology, which in this study could be crypto. In contrast, another study found no positive relationship between social influence and behavioral intention moderated by gender in the use of cryptocurrency in Indonesia (Novendra & Gunawan, 2017). According to Nurbarani and Soepriyanto (2022), demographic factors such as gender cannot moderate the relationship between subjective norms and the intent to invest in cryptocurrency assets.…”
Section: Gender Moderates Subjective Norms On Behavioral Intentions T...mentioning
confidence: 93%
“…Cabanillas et al (2021) stated that there was a relationship between subjective norms and gender-moderated intentions in the use of new technology, which in this study could be crypto. In contrast, another study found no positive relationship between social influence and behavioral intention moderated by gender in the use of cryptocurrency in Indonesia (Novendra & Gunawan, 2017). According to Nurbarani and Soepriyanto (2022), demographic factors such as gender cannot moderate the relationship between subjective norms and the intent to invest in cryptocurrency assets.…”
Section: Gender Moderates Subjective Norms On Behavioral Intentions T...mentioning
confidence: 93%
“…User Experience Questionnaire (UEQ) is a part of a usability test that aims to get a good impression of the user experience from a usability and experience perspective [38]. UEQ aims to provide a quick assessment by the user so that it can be properly and completely accepted by the user's perception where the perception in question is the impression of the product, the feelings that the user feels while using the product, and the behavior that arises when using a product [39] [40]. UEQ contains a questionnaire whose form supports user responses to display user feelings, impressions, and behavior directly when the product is used).…”
Section: G User Experience Questionnaire (Ueq)mentioning
confidence: 99%
“…Armed with the education they have, students are now able to read what opportunities are needed in entrepreneurship, including capital. In addition, most students who are engaged in running a technopreneurship business have good access to capital, whether it's from their parents, relatives, and others (Zarrouk et al, 2020;Novendra 2020).…”
Section: Coefficient Of Determination Test (R Square)mentioning
confidence: 99%